Embedded MEMS Platform for Structure Test and Characterization. (2015) - Brito, N.; Alves, F.S.; Cabral, J.; Gaspar, J.; Monteiro, J.; Rocha, L.A.
Abstract: The test and characterization of each individual manufactured MEMS structure is of major importance, both from the economic and quality standpoints[1–3] . A fast, cost-wise and easy to adjust testing system is a step forward on MEMS testing and characterization automation and cost reduction. This paper presents a processor-centric hardware assisted embedded solution to test MEMS structures using the built-in electrostatic actuation mechanisms. The system is based on the Leon soft-core processor, attached with the necessary MEMS specific hardware peripherals (capacitive readout circuit, ADC and DAC) to process the structure response to controlled actuation signals in real-time. The deterministic, parallel behavior of the dedicated hardware peripherals, allied to the simplicity of the sequential programming on a processor results in a well-suited solution to the necessary computational challenges. The system enables measurement of resonant frequency (Fr), quality factor (Q) and pull-in voltage (Vpi) within 1.5 seconds with repeatability better than 5 ppt (parts per thousand).